Development of communicative skills in foreign students - Hnatenko, S. A.; Jahnavi Uppala; Гнатенко, Світлана Анатоліївна (My University, 2021)
The primary task in the educational and upbringing processes at the Department of Language Training of Zaporizhia State Medical University is given to the development of communication skills by foreign students. Teaching foreigners the Ukrainian language at the department is implemented in the unity of several areas: teaching, research and educational work.